Geography and soccer: the athletic bilbao and the basque issue in the XIX-XXI centuries - Vilas Boas, Lucas Guedes (Geosaberes; Vol 8 No 15 (2017): May - AugDO - 10.26895/geosaberes.v8i15.570, 2017)
This article discusses the relationship between geography and soccer in the Basque Country, using as an example the soccer team Athletic Bilbao. In this context, the British hegemony in the nineteenth century was crucial to the popularization of soccer, because the most of modern sports has Anglophile origin. Despite the repression during the Franco dictatorship, the link between Athletic Bilbao and the Basque nationalism always maintained tight. Therefore, Athletic Bilbao was selected for this study because its governance policy differs from the dominant neoliberal pattern in recent times, because this team accepts in its cast only players born in the Basque Country or have been created in the Basque culture.
Keywords: Este artigo discute a relação entre geografia e futebol no País Basco, utilizando como exemplo a equipe futebolística Athletic de Bilbao. Neste panorama, a hegemonia inglesa no século XIX foi crucial para a popularização do futebol, pois a maioria dos esp